MENYUSUN BUSINESS PLAN DALAM RANGKA PENGEMBANGAN USAHA - Kristianto, Djoko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
Abstract Preparation of business plans to be an important communica-tion medium for the entrepreneur to explain the business profile to be developed. An increasingly competitive business conditions will require a leader figure who is able to face competition, so we can make preparations to solve these problems and we can indirectly determine the level of risk to be faced. Without planning, a com-pany will lose focus in achieving a goal. Planning helps managers answer some question as to what the a company target growth rate of corporate profits, whether the position of competitors and how the opportunities for profit. Keywords: Business Development, Business Planning, Entrepreneur-ship